2022
DOI: 10.3390/rs14153763
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Earth Observation-Based Drought Studies in Southeast Asia

Abstract: Drought is a recurring natural climatic hazard event over terrestrial land; it poses devastating threats to human health, the economy, and the environment. Given the increasing climate crisis, it is likely that extreme drought phenomena will become more frequent, and their impacts will probably be more devastating. Drought observations from space, therefore, play a key role in dissimilating timely and accurate information to support early warning drought management and mitigation planning, particularly in spar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 139 publications
0
8
0
Order By: Relevance
“…Brunner et al (2023) have detected changes in hydrological drought generating signatures over the Central Alps in recent periods compared to the past decades and found shifts in drought seasonality and severity in high-elevation catchments. Although previous regional-scale assessments have identified increasing trends in deficit volume and the spatial coverage of droughts across South Asia (Ullah et al 2022, Ganguli et al 2022a, Southeast Asia (Zhang et al 2021, Ha et al 2022), sub-Saharan Africa (Faustin Katchele et al 2017, Gebrechorkos et al 2022, and the Caribbean (Herrera et al 2018, Moraes et al 2022, a comprehensive assessment of change in streamflow drought onset, its deficit volume and spatiotemporal investigation of their combined trends have not yet investigated across the global tropics. Further, it is essential to understand nonlinear response between multivariate streamflow drought attributes, such as time to onset (i.e., seasonality) and severity (typically described by deficit volume) and their joint occurrences over time for environmental planning and monitoring (Blöschl et al 2017, Funk and Shukla 2020, Slater et al 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Brunner et al (2023) have detected changes in hydrological drought generating signatures over the Central Alps in recent periods compared to the past decades and found shifts in drought seasonality and severity in high-elevation catchments. Although previous regional-scale assessments have identified increasing trends in deficit volume and the spatial coverage of droughts across South Asia (Ullah et al 2022, Ganguli et al 2022a, Southeast Asia (Zhang et al 2021, Ha et al 2022), sub-Saharan Africa (Faustin Katchele et al 2017, Gebrechorkos et al 2022, and the Caribbean (Herrera et al 2018, Moraes et al 2022, a comprehensive assessment of change in streamflow drought onset, its deficit volume and spatiotemporal investigation of their combined trends have not yet investigated across the global tropics. Further, it is essential to understand nonlinear response between multivariate streamflow drought attributes, such as time to onset (i.e., seasonality) and severity (typically described by deficit volume) and their joint occurrences over time for environmental planning and monitoring (Blöschl et al 2017, Funk and Shukla 2020, Slater et al 2021.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of global warming, the global trend of drought is becoming increasingly serious. For example, in 2021, statistics from the United Nations Office for Disaster Risk Reduction showed that the average annual loss of agricultural drought in the United States alone reached 6.4 billion US dollars, and the average annual loss in Europe reached 9 billion US dollars 3 . In 2006–2017, the direct economic losses caused by drought in China averaged 88.230 billion US dollars annually, and the area of the crop affected was 169 million hm 2 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The soil moisture condition index (SMCI) illustrates SM condition considering the historical values, and the SMCI value range changes between 0 and 100, where the value close to 0 indicates extreme SM stress, while values nearby 100 describe the extremely wet condition. The PCI is a meteorological drought index to evaluate the concentration and variability of rainfall in time, which ranges from 0 to 100 based on variations in rainfall from highly unfavorable to optimal [29], [30], [31], [32].…”
Section: Introductionmentioning
confidence: 99%